Some natural history notes on Paraguayan armadillos (Xenarthra, Chlamyphoridae) Tolypeutes matacus and Euphractus sexcinctus - Paul Smith; Rebecca L. Smith; Matthew T. Owen (Xenarthra)
We report on some novel natural history observations of southern three-banded armadillo Tolypeutes matacus and six-banded armadillo Euphractus sexcinctus from Paraguay. These are: 1) a new band anomaly for an adult of T. matacus; 2) inclusion of the newly described subterranean termite Heterotermes lauralinearum Carrijo, 2020 (Rhinotermitidae) and the ant Atta vollenweideri (Forel, 1893) (Formicidae) in the Paraguayan diet of T. matacus; 3) the first reports of parasitism of T. matacus by fleas (Pulex irritans and potential lesion of Tunga perforans) in Paraguay; 4) identification of tracks of T. matacus in the field; and 5) the first documented record for E. sexcinctus in Ñeembucú department.